2011
DOI: 10.1016/j.nbd.2011.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of conditioned fear in the R6/2 mouse model of Huntington's disease is related to abnormal activity in prelimbic cortex

Abstract: Prefrontal cortex (PFC) dysfunction is common in patients with Huntington’s disease (HD), a dominantly inherited neurological disorder, and has been linked to cognitive disruption. We previously reported alterations in neuronal firing patterns recorded from PFC of the R6/2 mouse model of HD. To determine if PFC dysfunction results in behavioral impairments, we evaluated performance of wild-type (WT) and R6/2 mice in a fear conditioning and extinction behavioral task. Fear conditioning and extinction retrieval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
(74 reference statements)
0
15
0
Order By: Relevance
“…Moreover, PL neurons provide reinforcing feedback by sending robust projections to the amygdala, which may help drive freezing behavior. Furthermore, as the animals successfully extinguish fear responding, CS-induced firing of mPFC/PL neurons diminishes (38)(39)(40). Our data raise the intriguing possibility that this lasting depression of CS-induced firing in this mPFC subregion is an mGlu 3 -dependent process and could reflect a lasting depression of transmission from amygdala afferents.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, PL neurons provide reinforcing feedback by sending robust projections to the amygdala, which may help drive freezing behavior. Furthermore, as the animals successfully extinguish fear responding, CS-induced firing of mPFC/PL neurons diminishes (38)(39)(40). Our data raise the intriguing possibility that this lasting depression of CS-induced firing in this mPFC subregion is an mGlu 3 -dependent process and could reflect a lasting depression of transmission from amygdala afferents.…”
Section: Discussionmentioning
confidence: 63%
“…In vivo recordings have demonstrated that activity within the PL cortex, the region of the mPFC where we studied LTD, is correlated with freezing behavior during fear extinction (32,(38)(39)(40). During states of high fear and freezing, neurons within the PL will display robust firing in response to fear cues, such as a tone CS.…”
Section: Discussionmentioning
confidence: 99%
“…In tgHD rats, both reversal learning and fear conditioning were impaired [272], similar results were found in YAC128 mice [273, 274]. Similarly, R6/2 mice have difficulty extinguishing conditioned fear, an effect that correlated with altered activity in prefrontal cortex [275]. In a two-choice swim test, Q175 mice showed an increased latency in decision making [55].…”
Section: Dopamine Modulationmentioning
confidence: 78%
“…It already is clear from work on the R6/2 mouse model that information processing in the PFC is altered in HD mice [57]. In fact, abnormal neuronal activity in the prelimbic cortex, a region of the PFC with close ties to the amygdala, is correlated with reduced fear conditioning [275]. Although dysregulation of the corticostriatal circuit has been linked to motor and cognitive alterations in HD [36, 85, 86, 275, 311], very few studies have addressed the issue of DA system changes in HD associated with psychiatric disorders.…”
Section: Dopamine Modulationmentioning
confidence: 99%
“…The loss of correlated or synchronous firing among groups of cortical neurons across different models is a key point for HD because cooperative interactions among functionally related neurons, which are often manifest as synchronous oscillatory activity, shape behavioral output (9,14,84). In support of this view, dysregulation of prelimbic activity occurs in R6/2 mice during abnormalities in the extinction of fear conditioning (126).…”
Section: Altered Corticostriatal Processingmentioning
confidence: 97%